An Unmanned Surface Vehicle (USV) for Water Quality Monitoring Platform - Rahmat, Aqilah; Hanafi, Dirman (Evolution in Electrical and Electronic Engineering, 2023)
The goal of this project was to develop a low-cost unmanned surface vehicle (USV) water monitoring system. The project met its objectives since the overall cost was much cheaper than any other project available for the same purpose. The USV was also robust and controllable via Blynk apps, and the project was able to display some of the output data via the Blynk apps. The data is gathered under two distinct weather conditions. On a sunny day, the results show the temperature reading error rate is 1.88%, while on a rainy day, the error rate is 2%. This is considered to be fair. On a sunny day, the Ph reading error rate is 0%, whereas it is 6.4% on a rainy day. On a rainy day, this indicates that the sensor's accuracy is weakened. On a sunny day, the turbidity reading error rate is 99.35%, whereas on a rainy day, the error rate is - 99.17%, which is extremely error. This may be from the damage of the turbidity sensor. This shows that only the Ph and temperature sensors can be relied on this testing The job was performed in a systematic and precise manner. The design was built properly in AutoCAD software, and testing was carried out to collect data and confirm the results. In sum, the project's low cost makes it a realistic alternative for many organizations, and the USV's reliability and functionality make it a great instrument for water quality monitoring.